Kejahatan Bertopeng Agama: Sebuah Tinjauan Sosiologi Agama - Anwar, Saiful (Tarbawy : Jurnal Pendidikan Islam, 2017)
Religion wherever it is, always being replaced in high state of human life. Religion, as the source of all sources, is used as a tool to role human either vertically or horizontally. Karl Marx said that religion is a blessed heart against a cold and heartless world. Religion is a human medium to have more sympathy and empathy for others to live a warmer and friendlier life in peace. However, it cannot be denied that religion was once a sword used to commit genocide or mass annihilation by a group of humans against other human groups either directly or indirectly. Crusades, the middle-east war that is still going on are two examples of the dark events of human destruction wrapped by religion. Terrorism that occurs today is a deviation that is also wrapped by religion. These crimes are the result of a distortion of religious doctrine. Not only are physical destructive but also psychological and materialistic crimes. Cases of misappropriation of funds like the First Travel case are one of them. This paper will attempt to explore the phenomenon of crime in the name of Islam that happened lately in Indonesia. This paper will explore the phenomenon with a philosophical and social approach.